Increasing gas-turbine disks quality by improving their processing technology - Двирная, Ольга Зениковна; Шумилов, Александр Павлович (Technology audit and production reserves, 2014)
Constant tightening of the main characteristics of gas turbines has led to the need to develop and introduce new high-temperature materials with improved physical-mechanical properties, such as heat-resistant steel 15H12N2MFVAB-Sh (EP517-Sh). However, the lack of studies of key workability parameters of this material hinders its wide use in gas-turbine construction. The basic idea of the presented work is to create scientifically based technological processing conditions of tab grooves in the disks, made of steel EP517-Sh at maximum productivity increase of their processing method. Such conditions will lead to the roughness formation of the processed surfaces at the level of design requirements, useful compressive residual stresses and weakened surface layer that will significantly increase the tool joint reliability in the absence of any defects on the working surfaces of various tab grooves. For that, the regression equation of the processed surface roughness dependence on technological factors of the drawing process Ra = f (V, S, γ, HRC) was derived. The graphs of the considered dependencies were constructed for convenient analysis of the obtained results. Reliability of the conclusions on the work and recommendations on their introduction were confirmed by production researches.